The relationship between work environment factors and individual work performances among support staff from selected department at Sarawak Timber Industry Development Corporation Kuching / Maryanne Nicholas - Nicholas, Maryanne (2018)
This research examines the relationship between work environment factors and individual work performance among support staff from selected departments at Sarawak Timber Industry Development Corporation (STIDC) in Kuching, Sarawak. The main objective is to identify a correlation between the independent variables (social support, physical working conditions, job characteristics and communication practices) and its dependent variable (individual work performance). These information has been collected through questionnaires distributed to the support staff from selected departments. The data were analyzed using descriptive statistical analysis software method (IBM SPSS Statistics 20). The final results obtained from the highest correlation coefficient indicate that better individual work performance was associated to higher job characteristics. Employees tend to perform better if their job demands were excellently satisfied. Besides, on the medium results, support staff of STIDC agreed that social support, physical working conditions and communication practices also contribute to individual work performance with the highest mean on employees’ job characteristics as well.